Obtenção de polpa de manga em pó das variedades KENT e KEITT pelo processo de Spray-Drying - Adriano, Andreza Felipe (2019)
Mango is a fruit with a unique flavor, much appreciated and consumed in the country and in the world. However, due to its high perishability it is necessary to use processing techniques to extend their availability beyond the harvest season. The dehydration of the spray drying technique that transform the fruit pulp into powder maintaining most of its organoleptic characteristics and increasing the useful life. Thus, for the use of such a process it is necessary to use a carrier agent such as maltodextrin. Thus, the objective of this work was to evaluate the powder of mango pulp of the Kent and Keitt varieties, characterizing its physico-chemical, rheological and morphological characteristics. Mango pulps were generously provided by Embrapa Agroindústria Tropical, and mangoes were obtained in the city of Petrolina (PE). The experimental design assays were carried out with three different concentrations of maltodextrin (10, 20 and 30%), where, after analysis, the pulp mixed with 30% maltodextrin presented a powder with lower moisture, higher amount of ascorbic acid, for both varieties. the analysis showed that in this concentration of maltodextrin it favors the decrease of the moisture content, the water activity, the parameter b* of color and, consequently, increases the soluble solids, sugars, total acidity and the L* parameter of the pulp powder. The stability study of the powder was evaluated for 90 days using two different packages (transparent and laminated), where the laminate was more suitable for preservation, since the morphological analysis of the powder in this package showed smooth particles with amorphous properties, and still tending to decrease the particle size with increasing maltodextrin concentration. These characteristics were confirmed by x-ray diffraction analysis, whereas in the zeta potential analysis it was shown that the increase in the concentration of maltodextrin produces more negatively charged powder, which favors a lower agglomeration of the powder. The glass transition temperature analysis also showed that this increase in the concentration of maltodextrin also increases the transition temperature. Among the models studied, the GAB model was the one that best adjusted the isotherms of the mango pulps of the two varieties, presenting type III graphs, characteristic for fruit pulps. The rheological analyzes of the powder showed a characteristic of powder with tendency to the cohesive flow of fuidez.